DNase I-Responsive Calixpyridinium-Mediated DNA Aggregation - Wang, Kui (Langmuir : the ACS journal of surfaces and colloids, 2019)
In this work, cationic macrocyclic calixpyridinium was employed as a new strategy to condense DNA. Moreover, the degradation of DNA by DNase I could lead to the calixpyridinium-DNA supramolecular aggregates being dissipated. Therefore, the present system is potentially applicable as the targeted drug delivery model at DNase I-overexpressed sites